E-002 Safety of Retained Microcatheters: An Evaluation of RF Heating in a Nitinol Braided Endovascular Catheter at 1.5T and 3T. (14th July 2013) - Losey, A; Lillaney, P; Martin, A; Halbach, V; Cooke, D; Dowd, C; Higashida, R; Saloner, D; Wilson, M; Saeed, M; Hetts, S
Abstract : Purpose: The use of ethylene-vinyl alcohol copolymer (EVOH, Onyx) for liquid embolisation of cranial vascular lesions has occasionally resulted in microcatheter fragments unintentionally remaining in situ in patients following endovascular procedures. Undergoing subsequent diagnostic MRI examinations poses a safety concern due to potential radiofrequency (RF) heating mediated by the metallic braid incorporated into the microcatheter. We sought to assess heating of a microcatheter commonly used to deliver Onyx in a phantom. Methods: A 1.9F nitinol braided microcatheter (eV3 Echelon™-14, Irvine, CA) was embedded in a polyacrylamide phantom with five fluoroptic temperature probes placed along the length of the microcatheter and an additional background sensor. The phantom was scanned using a fast spin echo (FSE) sequence at average specific absorption rate (SAR) levels from 0.25 to 4.0 W/kg. Further scanning was performed using 2-minute clinical scans: T1 FSE, T2 FSE, DWI, T2 FLAIR, 3D-SPGR and b-SSFP. The scan that produced the most heating was repeated over a 15-minute acquisition. The experiments were then repeated with catheter fragment lengths of 9cm, 18cm, 36cm and 72cm. Experiments were performed on both 1.5T (Philips Achieva, Cleveland, OH) and 3T (GE Discovery 750w, Milwaukee, WI) clinical scanners. Results: The maximal heating for the nitinol braided catheter immersed 93cm occurred at 20cm proximal to the tip using the T1 FSE sequence at 1.5 T. Maximal heating at 3T occurred using the b-SSFP sequence at the same position. The maximal temperature rise during a 2-minute scan was 0.84C at 1.5T and 0.45C at 3T. Figure 1 shows the temperature changes along different points on the catheter during a 15-minute T1 FSE sequence at 1.5T. The same scans for fragment lengths of 9cm, 18cm, 36cm and 72cm produced maximal temperature (C) rises of 0.68, 0.80, 1.70 and 1.07 at 1.5T, respectively. The temperature changes during a 15-min b-SSFP sequence at 3T for these fragment lengths were 0.66, 0.83, 1.07 and 0.72, respectively. Conclusions: Heating of nitinol braided microcatheters occurred during diagnostic MR scanning and was a function of SAR level and geometric considerations. SAR and time limitations are proposed for patients with this microcatheter entrapped in their vasculature. Although the catheter displayed higher heating levels at 1.5T relative to 3T at a given SAR, it should be noted that there are most likely differences between the SAR models on the two scanner interfaces. Furthermore, the 3T scanner used for this study had a wider diameter bore. Disclosures: A. Losey: None. P. Lillaney: None. A. Martin: None. V. Halbach: None. D. Cooke: None. C. Dowd: None. R. Higashida: None. D. Saloner: None. M. Wilson: None. M. Saeed: None. S. Hetts: None.